Plasmodium vivax and human hexokinases share similar active sites but display distinct quaternary architectures - Srivastava, Shanti Swaroop (IUCrJ, 2020)
Malaria is a devastating disease caused by a protozoan parasite. It affects over 300 million individuals and results in over 400 000 deaths annually, most of whom are young children under the age of five. Hexokinase, the first enzyme in glucose metabolism, plays an important role in the infection process and represents a promising target for therapeutic intervention. Here, cryo-EM structures of two conformational states of Plasmodium vivax hexokinase (PvHK) are reported at resolutions of ∼3 Å. It is shown that unlike other known hexokinase structures, PvHK displays a unique tetrameric organization (∼220 kDa) that can exist in either open or closed quaternary conformational states. Despite the resemblance of the active site of PvHK to its mammalian counterparts, this tetrameric organization is distinct from that of human hexokinases, providing a foundation for the structure-guided design of parasite-selective antimalarial drugs.